2021
DOI: 10.4103/jpbs.jpbs_324_20
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Evaluation of Prescription Pattern in Glaucoma Clinic of a Tertiary Care Hospital

Abstract: A BSTRACT Background: Glaucoma is a chronic, gradual and progressive eye disorder characterized by visual loss and involving the typical changes in optic nerves and associated structures. Currently, the mainstay treatment lies in the reduction of intraocular pressure (IOP) involving the usage of two or three medications concurrently. However, prescription pattern of antiglaucoma drugs remains largely unstudied so far. Therefore, there is a dire need of drug utilization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In our study, we found that the mean drugs in the prescriptions from both centers were comparable: 1.98 ± 0.99 and 1.92 ± 1.11, in 1.41 ± 0.59 and 1.51 ± 0.64, from the public and private hospitals, respectively. In a naturalistic evaluation of glaucoma prescription patterns from the glaucoma clinic of a tertiary care hospital in the same region, Niraj et al 6 had reported that the mean drugs in the prescriptions from their hospital was 2.18 ± 1.68, while the same was 5.04 ± 1.52 in cases referred to their center from other hospitals. While the five drugs to a prescription may be explained by the fact that only those patients who are not controlled on maximal medical therapy (MMT) are referred to a tertiary care center, it may be interesting to compare the prescription patterns of glaucoma specialists with those from general ophthalmologists to better understand drug utilization patterns in the region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that the mean drugs in the prescriptions from both centers were comparable: 1.98 ± 0.99 and 1.92 ± 1.11, in 1.41 ± 0.59 and 1.51 ± 0.64, from the public and private hospitals, respectively. In a naturalistic evaluation of glaucoma prescription patterns from the glaucoma clinic of a tertiary care hospital in the same region, Niraj et al 6 had reported that the mean drugs in the prescriptions from their hospital was 2.18 ± 1.68, while the same was 5.04 ± 1.52 in cases referred to their center from other hospitals. While the five drugs to a prescription may be explained by the fact that only those patients who are not controlled on maximal medical therapy (MMT) are referred to a tertiary care center, it may be interesting to compare the prescription patterns of glaucoma specialists with those from general ophthalmologists to better understand drug utilization patterns in the region.…”
Section: Discussionmentioning
confidence: 99%
“…The irrational and inappropriate use of medication is a major concern worldwide, across disciplines, and glaucoma is no exception. 2 – 6 …”
Section: Introductionmentioning
confidence: 99%